Violência infantil: o perfil epidemiológico no Brasil a partir de dados do sistema de informação de agravos de notificação (SINAN) - João Victor de Paula Correia (2023)
Child violence is a social and public health phenomenon, which impacts children's development and, consequently, adult life. The present study aimed to describe reported cases and compare notification rates of types of violence by sex and age groups, from 2011 to 2021. Secondary data from the Notifiable Diseases Information System were used regarding cases reported for each year in the period . The databases were analyzed in relation to size and structure. Data preparation was via semi-automated download, followed by analysis of completeness, duplication and treatment. The structuring of this base preserved the space-time structure. After removing duplicates, the proportions of cases were obtained to characterize the occurrence of violence, the victim and the aggressors. The data collected from the victims were: Age, sex, race/color, presence of disability/disorder. Occurrence data included: place of occurrence, recurrence of violence, type of violence and means of aggression. The aggressor variables were: number of people involved, bond with the victim of violence and suspected alcohol use. The data were subjected to exploratory analysis, obtaining summary measures of notification rates for Brazil and stratified by sex and age group (0-4 years; 5-9 years of age). The proportions of violence were presented according to variables of the occurrence, the victim and the aggressor to characterize reports of violence in Brazil. The total number of cases of child violence reported in children aged 0 to 4 years was 254,980 (63.5%) and 146,577 (36.5%) in children aged 5 to 9 years. Recidivism of violence occurred was 99,324 (31.7%) and was more frequent in girls of both age groups. Mothers 189,076 (52.5%) and fathers 121,926 (34.6%) had the highest proportions of notifications. The highest notification rates of child violence were of neglect in the age group from 0 to 4 years of age in both sexes, 72,640 (46.4%) in females and 83,782 (53.6%) in males. Rates of sexual violence were the second highest for female children in both age groups. Psychological and sexual violence were approximately 2 and 3.5 times more reported among girls, respectively in the two age groups. Reporting rates of physical violence and neglect were similar by sex in both age groups. The reasons for the reporting rates of physical, psychological, neglect and sexual violence among female and male victims revealed that, in the 0-4 age group, the highest rates were observed for girls in most years, except for neglect, the rates of which were around 10% lower in girls, and in the age group of 5 to 9 years the highest rates were observed for boys, in most years, except for sexual and physical violence. Our findings revealed that sexual and psychological violence were the ones with the highest notification rates among girls, with the residence being the place of greatest occurrence of notification and those responsible for the child being the main aggressors.